Nanoscale temperature sensors based on MIM waveguide coupling and ring-embedded nanostructures - Chen, Hongfu; Yan, Shubin; Cao, Yuhao; Jiang, Wen; Yan, Xiaoran; Wang, Chong; Liu, Guang; Xu, Aiwei; Wu, Taiquan; Li, Yuntang (Frontiers in Physics, 2024)
This study presents a novel refractive index sensor based on Fano resonance, incorporating a metal-insulator-metal (MIM) waveguide coupled with a circular ring structure (CRC). Using finite element method analysis, we investigated the propagation properties of the sensor. To evaluate their influence on sensor performance, we systematically varied the parameters of each Circular Resonant Cavity structure component, including the refractive index, employing a controlled variable approach. At its optimal configuration, the sensor achieves a maximum sensitivity of 3,240 nm/RIU and a figure of merit (FOM) of 57.9. With its high sensitivity, straightforward design, and suitability for temperature detection, the refractive index sensor holds promise for diverse applications.